TAK1-TABs Complex: A Central Signalosome in Inflammatory Responses - Xu, Yan-Ran; Lei, Cao-Qi (Frontiers in Immunology, 2021)
Transforming growth factor-β (TGF-β)-activated kinase 1 (TAK1) is a member of the MAPK kinase kinase (MAPKKK) family and has been implicated in the regulation of a wide range of physiological and pathological processes. TAK1 functions through assembling with its binding partners TAK1-binding proteins (TAB1, TAB2, and TAB3) and can be activated by a variety of stimuli such as tumor necrosis factor α (TNFα), interleukin-1β (IL-1β), and toll-like receptor ligands, and plays essential roles in the activation of NF-κB and MAPKs. Numerous studies have demonstrated that post-translational modifications play important roles in properly controlling the activity and stability of TAK1-TABs complex according to the indicated cellular environment. This review focuses on the recent advances in TAK1-TABs-mediated signaling and the regulations of TAK1-TABs complex by post-translational modifications.